If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(z-4)=2(z-7)
We move all terms to the left:
5(z-4)-(2(z-7))=0
We multiply parentheses
5z-(2(z-7))-20=0
We calculate terms in parentheses: -(2(z-7)), so:We get rid of parentheses
2(z-7)
We multiply parentheses
2z-14
Back to the equation:
-(2z-14)
5z-2z+14-20=0
We add all the numbers together, and all the variables
3z-6=0
We move all terms containing z to the left, all other terms to the right
3z=6
z=6/3
z=2
| r-46/8=6 | | 5=(2x+6) | | -4(v+7)=-24 | | -4(3x-2)=-2(5x-7)+4 | | 7(n-86)=14 | | 4(2p-1)=3(p+2) | | 20x-8=17x+1 | | 5(2x-1)=3x+30 | | 12=b/3×9 | | -2=d-14 | | -4+-9u=23 | | z.z-12=30 | | 84=7(w+2) | | 24+2u=64 | | 14.8=n-3.0 | | 3n-14=-2+49 | | 5(2p-1)=3(p+2) | | 3=2-n/5 | | 15+5g=50 | | 6(1+8a)=246 | | 9m-3=19-2m | | 3n-14=2n+49 | | 8=-20+7k | | 12r+7=15r+1 | | 4(w-81)=12 | | 7+4x=47 | | x/2+40=3x/4 | | d/4+22=24 | | -20x=-35 | | 12.45-3.2b=-18.15-5.2b | | 6x+14=7x=5 | | 6x-9=8x+16 |